2019
DOI: 10.5812/jjm.68183
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Panton-Valentine Leukocidin Harboring Hospital-Associated Methicillin-Resistant Staphylococcus aureus in Septicemic Children, Northeastern Iran, Bojnurd

Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) is responsible for an increasing number of serious hospital-and community-acquired infections in adults and children. Sepsis caused by S. aureus is one of the major health problems associated with treatment failure in adults; however, its clinical outcomes, the rate of treatment failure, and its molecular epidemiology are poorly understood. Objectives: The objective of this study was to evaluate the molecular epidemiology of Panton-Valentine Leukoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…As discussed in many previously published articles, the source of vanA gene can be vancomycin-resistant enterococci or other vancomycin-resistant staphylococci (20). If the VRSA isolates are the source of resistance genes, we should find the same clones in different samples; but regarding the diversity of genetic clones of our isolates, we may Predict the independent acquisition of resistance in different isolates.…”
Section: Discussionmentioning
confidence: 98%
“…As discussed in many previously published articles, the source of vanA gene can be vancomycin-resistant enterococci or other vancomycin-resistant staphylococci (20). If the VRSA isolates are the source of resistance genes, we should find the same clones in different samples; but regarding the diversity of genetic clones of our isolates, we may Predict the independent acquisition of resistance in different isolates.…”
Section: Discussionmentioning
confidence: 98%
“…The pathogenesis of this bacterium is further accentuated by the prevalence of antibiotic resistance among S. aureus isolates, often necessitating the use of more sophisticated treatment options [12]. The [13][14][15]. In some studies, no significant relationship has been observed between gender and the rate of MRSA infection but in some other studies, they have stated that this infection is more common in young people, and in some other studies, they have found this to be the case in the elderly [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The antibiogram test was performed using tetracycline (TET), cefoxitin (CEF), moxifloxacin (MOX), levofloxacin (LEV), erythromycin (ERY), rifampicin (RIF), clindamycin (CLN), penicillin (PEN), gentamicin (GEN), minocycline (MIN), trimethoprim/sulfamethoxazole (COT), vancomycin (VAN), and linezolid (LIN) antimicrobial disks using the Kirby-Bauer disk diffusion method (MASTDISCS TM , UK) based on Clinical and Laboratory Standards Institute guidelines (14).…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%